1997
DOI: 10.1093/jn/127.9.1875s
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Set-Points: Determination and Adjustment

Abstract: It is proposed that body weight, like body water and body temperature, is physiologically regulated. In the case of body weight, coordinated adjustments in both the intake and expenditure of energy serve to stabilize the weights of individuals at a specified level and to resist their displacement from this level. Obese individuals also display these behavioral and metabolic adjustments to weight perturbations and thus appear to actively resist efforts to reduce their weight from the elevated levels they ordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(125 citation statements)
references
References 23 publications
4
116
0
4
Order By: Relevance
“…Previous studies have reported increased adiposity and body weight in male and female offspring of mothers fed an SFA-rich diet during pregnancy and lactation in different rat models (9,27,37). It has also been shown earlier that rodents, like humans, can regulate their food intake and energy expenditure to maintain a set body weight (33). This would explain the reduction of food intake in the case of S/S and C/S offspring.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have reported increased adiposity and body weight in male and female offspring of mothers fed an SFA-rich diet during pregnancy and lactation in different rat models (9,27,37). It has also been shown earlier that rodents, like humans, can regulate their food intake and energy expenditure to maintain a set body weight (33). This would explain the reduction of food intake in the case of S/S and C/S offspring.…”
Section: Discussionmentioning
confidence: 85%
“…The 'set point' has been proposed as a body weight that is physiologically regulated, where intake and expenditure of energy are adjusted in order to maintain this level. 5,6 Supporting this are observations that deprived animals and humans usually re-gain their weight after dietary restraints are removed. 6,7 There are a number of central effector pathways in the hypothalamus involved in regulating appetite which are thought to be influenced by body adiposity, resulting in long-term stability of fat stores.…”
Section: Introductionmentioning
confidence: 93%
“…5,6 Supporting this are observations that deprived animals and humans usually re-gain their weight after dietary restraints are removed. 6,7 There are a number of central effector pathways in the hypothalamus involved in regulating appetite which are thought to be influenced by body adiposity, resulting in long-term stability of fat stores. 1 The concept that humoral signals generated in proportion to body fat stores, act in the brain to regulate body weight and adiposity 8 was strengthened by the discovery of mutations in obese mice 9,10 and, subsequently, the discovery of leptin.…”
Section: Introductionmentioning
confidence: 93%
“…However, food intake was less in male and female FF than in male and female FC and CON (Figure 4). Rats are known to regulate caloric intake when fed a hypercaloric diet, 18 and despite reduced dietary intake, fat intake remained 4-fold higher in FF rats compared with controls. When dietary intake in offspring was converted to energy, the average daily gross energy intake increased only in male FF (average daily intake after 60 days of age, 393.07Ïź6.66 kJ, nÏ­5 versus CON, 362.22Ïź5.54 kJ, nÏ­10; PÏœ0.05), and this is a likely explanation for the increase in body weight by 180 days.…”
Section: Endothelium-dependent Relaxationmentioning
confidence: 99%